LIGHT CURVE OF NOVAE IN THE “OUTBURST AMPLITUDE, ENVELOPE RADIUS” COORDINATES AS THE BASIS FOR THE CLASSIFICATION OF NOVAE ON TYPES - Rosenbush, A. E. (Одеські астрономічні публікації, 2017)
The representation of light curves of novae in the ”outburst amplitude, envelope radius” coordinates reveals the existence of five types of novae. In addition to the outburst amplitude and shape of the whole light curve, every type is possibly characterized by the shape of ejected envelope and some other common physical characteristics. The outburst amplitude in the range from 12 to 15m in the DQ Her type is likely to depend on the inclination of the binary orbit and therefore on the inclination of the dust belt that reaches its maximum optical thickness on a distance of about 5.9×1014 cm. The dust condensation at a definite belt inclination can lead to a temporal increase of a nova visual light up to 2m (V 1668 Cyg, DN Gem) at the transition instead of its decline.